QUALITY OF AUTOCHTHONOUS SICILIAN PLUMS - F. Sottile; V. Girgenti; N.R. Giuggioli; M.B. Del Signore; C. Peano (Chiriotti Editori, 2015)
Thirty four plum local varieties and accessions obtained from different growing area of the Sicilian island were analyzed for their qualitative and nutraceutical properties and three commercial cultivar were used as references. These properties included the fruit fresh weight (g), the pulp firmness (FFF), the total soluble solids (TSS), the titratable acidity (TA), the total anthocyanins, the phenolics content and the antioxidant activity. This preliminary study showed significantly differeces among the plums; Zuccarato giallo and Prunu Niuru presented TSS higher than the commercial cultivars (24.9 and 21.6 °Brix respectively) and interesting data obtained on the nutraceutical compounds values suggested these local cultivars as sources of polyphenols (Zuccarato giallo with 663 mg GA/100 gFW) and natural antioxidants (Pruno Regina with 47.46 Fe2+/100 gFW). The characterization of these plums could represent also an important resource for the international activity in the genetic improving and the collection of the more interesting quality traits could be useful for improving the Prunus database actually in use.